Durability of clinical and immunologic responses to extended low-dose interleukin-2 therapy in patients with refractory chronic graft-versus-host disease - Donato, Veronica; Kim, Haesook T.; Stowe, Peter; Reynolds, Carol G.; Ritz, Jerome; Koreth, John; Whangbo, Jennifer S. (Frontiers in Immunology, 2022)
Chronic graft-versus-host disease (cGVHD) remains a frequent cause of non-relapse morbidity and mortality after allogeneic hematopoietic stem cell transplantation. In our single center trials of low-dose interleukin-2 (LD IL-2), the immunomodulatory properties of regulatory T cells (Tregs) have been harnessed to treat steroid-refractory cGVHD (SR-cGVHD) safely and effectively in adults and children. In these trials, 50-60% of patients showed clinical improvement of their cGVHD manifestations with partial responses at the primary response endpoint of 8-12 weeks. Many patients continued extended duration LD IL-2 therapy and achieved deeper clinical responses, including some complete responses. However, the durability of the clinical and immunologic improvement following IL-2 discontinuation has not been reported previously. We examined 20 adult and 2 pediatric patients who received extended duration LD IL-2 for a median of 103 weeks (range, 21-258) and had stable improvement or resolution of their cGVHD symptoms before discontinuing LD IL-2 therapy. The median follow-up after stopping IL-2 was 203 weeks (range 92-599). During this time, 16 patients (73%) were able to wean off all systemic immunosuppression without disease flare or progression. Among 13 patients with available immune cell data, the median fold change in absolute Treg count was 0.58 between 1 to 10 weeks after stopping IL-2 whereas CD4+ conventional T-cell (Tcon) and CD8+ T-cell numbers remained stable. Despite a decline in Treg numbers after IL-2 discontinuation, Treg numbers remained above the pre-treatment baseline. In addition, many patients had sustained clinical improvement after stopping IL-2, suggesting that extended IL-2 therapy can lead to immune tolerance.